Antiproliferatif Ekstrak Metanol Daun Dianella nemorosa Lam. (Liliaceae) terhadap Sel Kanker MKN45 dengan Menggunakan Metode WST-1 - Aditya K. Karim; Sismindari Sismindari (Jurusan Biologi FMIPA Universitas Cenderawasih, 2011)
Dianella nemorosa Lam. was known containing alkaloids, terpenoid, phenolic compouds and tanin. Antiproliferative effect of D. nemorosa leaves methanol exctract, which demonstrated to have an in vitro cytotoxic effect on cancer cell line. The aim of research was examined the effect antiproliferative methanol extract of D. nemorosa leaves against MKN45 (gastric cancer) cell line. Leaves powder extracted using methanol. Antiproliferative effect was determined by Cell Proliferation Reagents WST-1 ((2-(4-iodophenyl)-3-(4-nitro-phenyl)-5-(2,4-disulfophenyl)-2H-tetrazolium monosodium salt). Test for 1h, 2h, and 4h after incubated for 72h was done. The result of this research showed that methanol exctract from D. nemorosa possessed remarkable no had antiproliferative activity against MKN45 cell line. The result indicated methanol extract of D. nemorosa leaves selective inhibitory effect or antiproliferative against cell line. Key words: Dianella nemorosa, Antiproliferative, MKN 45, and WST-1